Fake it 'til you make it: visual and behavioural ecology of poison frog mimicry - McEwen, Brendan (My University, 2025)
Aposematic signals advertise chemical defense or other forms of unprofitability to predators and may be parasitized by dishonest signallers through Batesian mimicry. Warning signals do not provide perfect avoidance, however, meaning many aposematic phenotypes evolve to balance between signal saliency and mitigating detection. For Batesian mimics the cost of a predator encounter should be greater, which begs the question of whether imperfect mimicry leads Batesian mimics to exhibit more muted signals than their models. I sought to test this hypothesis and other related hypotheses using the Ameerega-Allobates poison frog mimicry complex native to the Ecuadorian Amazonian rainforest. In Chapter 2 I found that, while many elements of the mimic’s signal were less salient than in the model, the mimic had higher detectability than the model. I also found that saliency discrepancies across colour patches produced variation in detectability across different body postures and viewing angles in both species. In Chapter 3 I turned my focus to how the balance between cryptic and salient signal elements changes across ontogeny, and how shifts in that balance may affect detectability. I found that both species undergo ontogenetic colour change, with the mimic improving in resemblance to the model as it developed and the model refining its aposematic signal as it grew. These colour changes impacted the crypsis efficacy of the mimic in that different colour stages had differential detectability. In Chapter 4 I tested for behavioural associations with the ontogenetic increase in mimetic fidelity in Al. zaparo. I found that colouration alone did not explain variation in behaviour, and that body size and environmental conditions impacted boldness and activity.
Keywords: Visual Ecology; Batesian Mimicry; Aposematism; Crypsis; Poison Frogs; Tropical Ecology; Detection Experiments; Behavioural Ecology; Antipredator Colouration; Defensive Colouration; Multifunctional Colour; Multicomponent Signals